Vaccine-related pain: randomised controlled trial of two injection techniques. Issue 12 (8th August 2007) - Ipp, Moshe; Taddio, Anna; Sam, Jonathan; Gladbach, Morton; Parkin, Patricia C
Abstract : Objective: To compare acute pain response during immunisation in infants using a slow standard of care injection technique versus a rapid pragmatic technique. Design: Randomised controlled trial. Setting: Single-centre, urban paediatric primary care practice. Subjects: Healthy infants 4–6 months of age receiving their routine DPTaP-Hib immunisation. Interventions: Standard of care group: slow aspiration prior to injection, slow injection and slow withdrawal. Pragmatic group: no aspiration, rapid injection and rapid withdrawal. Main outcome measures: Immediate infant pain measured by the Modified Behavior Pain Scale (MBPS), crying and parent/paediatrician visual analogue scale (VAS). Results: 113 infants participated; there were no observed differences in age, birth order or prior analgesic use. Mean MBPS scores (95% confidence interval (CI)) were higher (p<0.001) for the standard group compared to the pragmatic group, 5.6 (5 to 6.3) vs 3.3 (2.6 to 3.9). The standard group was more likely to cry, 47/57 (82%) vs 24/56 (43%), to cry longer, median (interquartile range (IQR)) 14.7 s (8.7–35.6) vs 0 s (0–11.30), and to take longer to have the vaccine injected, median (IQR) 8.8 s (7.9–10.3) vs 0.9 s (0.8–1.1), p<0.001 for all comparisons. The median (IQR) VAS scores by parents and paediatricians were higher for the standard group: VAS parent, 3.5 (1.6–5.5) vs 1.9 (0.1–3.1) and VAS paediatrician, 2.8 (2.0–5.1) vs 1.4 (0.2–2.4). There were no adverse events. Conclusion: Immunisation using a pragmatic rapid injection technique is less painful than a slow standard of care technique and should be recommended for routine intramuscular immunisations.